Lowering the C-H bond activation barrier of methane by means of SAC@Cu(111): periodic DFT investigations - Bhati, Meema; Dhumal, Jignesh; Joshi, Kavita (New Journal of Chemistry, 2021)
Methane has long captured the world's attention for being the simplest yet one of the most notorious hydrocarbons. Exploring its potential to be converted into value-added products has raised compelling interest. In the present work, we have studied the efficiency of single-atom catalysts (SACs) for methane activation employing density functional theory (DFT). The climbing image-nudged elastic band (CI-NEB) method is used in tandem with the improved dimer (ID) method to determine the minimum energy pathway for the first C-H bond dissociation of methane. Our study reported that the transition-metal doped Cu(111) surfaces enhance the adsorption, activate the C-H bond, and reduce the activation barrier for first C-H bond cleavage of methane. The results suggest Ru-/Co-/Rh-doped Cu(111) as promising candidates for methane activation with a minimal activation barrier and a less endothermic reaction. For these SACs, the calculated activation barriers for the first C-H bond cleavage are 0.17 eV, 0.24 eV, and 0.26 eV respectively, which is substantially lower than 1.13 eV, the activation barrier for Cu(111).

Remarkable SO2 and H2S resistant ability on CO oxidation by unique Pd/WO3 3D hollow sphere nanocatalyst: correlating structure-activity relationships on SO2 exposure - Jeyavani, Vijayakrishnan; Kondhekar, Deepali; Bhati, Meema; Dev, Sahil; Joshi, Kavita; Devi, R. Nandini; Mukherjee, Shatabdi Porel (ACS Applied Energy Materials, 2024)
We report a simple inorganic route for synthesizing a Pd/WO3 3D hollow sphere nanocatalyst, where Pd nanoparticles are encapsulated and well distributed on porous tungsten oxide nanospheres. The synthesis protocol has advantages, as it requires no surfactant or stabilizing agent, Pd loading is easily tuned, and the as-synthesized nanomaterials can be directly used as catalysts for the CO oxidation reaction. The synthesized nanocatalyst exhibited 100% CO to CO2 conversion efficiency at 260 degrees C. In addition, the nanocatalyst demonstrated remarkable SO2 (3 ppm) tolerance during the CO oxidation reaction for prolonged SO2 sulfation of 1-21 h at 260-400 degrees C. This represents the longest SO2 exposure time reported to date based on a single metal Pd/support-based nanocatalyst. No decrement in CO conversion efficiency was observed even after SO2 (3 ppm) treatment for 21 h for the first time based on a single metal Pd-based nanocatalyst. Moreover, the synthesized nanocatalyst shows H2S (4 ppm), even in situ H2S tolerance during the CO oxidation reaction at 260 degrees C for 1-3 h and exhibited less sensitivity to prolonged and stringent sulfur exposure, with the highest H2S concentration and maximum 100% CO to CO2 conversion efficiency obtained after H2S treatment for the first time based on a Pd-based nanocatalyst to the best of our knowledge. The composition and structure of the R-Pd/WO3 nanocatalyst were not much influenced, even after the prolonged SO2 and H2S exposure during the CO oxidation reaction, as verified from spent catalyst analysis. Finally, our DFT-based model provides insights into understanding the observed sulfur resistance on Pd/WO3 by analyzing the underlying electronic structure. Therefore, our strategic synthesis methodology will open up many opportunities to select Pd/metal oxide-based nanomaterials for designing highly efficient, stable, and SO2/H2S-resistant nanocomposite catalyst.
Keywords: CO oxidation; DFT calculation; nanocatalyst; palladium (Pd); SO2 andH(2)S resistant ability; structure-activityrelationships; tungstenoxide (WO3)

Sequential nitro-michael addition and reductive cyclization cascade reaction for diastereoselective synthesis of multifunctionalized 3,3′-pyrrolidinyl-spirooxindoles - Nichinde, Chandrakant B.; Bhati, Meema; Girase, Amardipsing S.; Patil, Baliram R.; Chaudhari, Suryakant S.; Gamidi, Rama Krishna; Joshi, Kavita; Kinage, Anil K. (European Journal of Organic Chemistry, 2025)
In this investigation, we elucidated, one-pot two stage efficient synthesis of multifuctionalized spiro[oxindole -3,3 `-pyrrolidine]. The methodology proceeds via organocatalyzed nitro-Michael addition reaction between indolylidenecyanoesters and nitroalkanes to formed nitro-Michael adduct which transformed into multifunctionalized 3,3 `-pyrrolidinyl-spirooxindoles by metal catalyzed reductive cyclization cascade. DFT investigations were conducted to elucidate the mechanism underlying the preferential reduction of the nitro group, with subsequent attack on the nitrile and ester groups remain inert throughout the reaction process. The approach is operationally simple, easily scalable, exhibits compatibility with readily accessible starting material and catalysts, thereby emphasizing cost-effectiveness.
Keywords: 3 `-pyrrolidinyl spirooxindoles; DFT study for regioselective cyclization; Diastereoselective 3; organocatalysis; Pd/C catalysed partial reductive spirocyclization

When facets meet impurities: Trace gas dominance over CO2 adsorption on ZnO - Bhati, Meema; Joshi, Kavita (Applied Surface Science, 2026)
The catalytic hydrogenation of CO2 to methanol using Cu-ZnO/Al2O3 (CZA) is a key route for sustainable chemical production, when coupled with CO2-rich industrial off-gases. However, trace secondary gases, though present only at ppm levels, can poison active sites and suppress catalytic performance. In this work, we employ periodic density functional theory (DFT) to investigate interactions of H2S, SO2, NO2, NO, CO and CH4 with ZnO surfaces:(10(-)10), (10(-)11), (11(-)20), (10(-)13), and (11(-)22), and compared their adsorption pattern with CO2, the principle component of methanol synthesis. H2S dissociates on all the surfaces, SO2, and NO2 are chemisorbed, CH4 remains physisorbed, and NO, CO, and CO2 exhibit facet-dependent adsorption. Electronic structure analysis reveal that chemisorption occurs when surface energy states near the Fermi level overlap with HOMO of adsorbate, enabling charge transfer, whereas physisorption lacks such overlap. The adsorption strength follows the order: H2S SO2 NO2 NO CO CO2 CH4, suggesting that sulfur and nitrogen containing species exhibit strong chemisorption and compete with CO2 for active sites, potentially impacting the efficiency of methanol synthesis. These insights provide an atomic scale understanding of impurity-surface interactions and highlight potential role of ZnO as an efficient feed stock purifier for CO2-rich gas streams.
Keywords: CZA catalyst; flue gases; Valorization of CO2; ZnO